The Effect of Profitability, Liquidity, and Risk on Capital Buffers in Conventional Banking Companies Listed on The Idx in 2020 – 2022 - Bangkit Pangestu; Kartini Kartini (Jurnal Syntax Transformation, 2023)
This research aims to test and analyze the influence of profitability, liquidity and risk on capital buffers in banking companies listed on the IDX in 2020 - 2022. The independent variables in this research are ROA, LDR and NPL. Meanwhile, the independent variable in this research is Capital Buffer. The research approach used is quantitative. The data is secondary data in the form of company financial reports taken from the website www.idx.com. The sampling technique uses a purposive sampling method. The method used in this research is multiple regression analysis, using the SPSS version 25 application. The data analysis technique used in this research is statistical and descriptive analysis. The research results show that profitability has no effect on the capital buffer, liquidity has a positive and significant effect on the capital buffer, and risk has a negative and significant effect on the capital buffer.